Estrategias de adaptación de los padres en la crianza de niños con Síndrome de Down que acuden al Centro de Educación Básica Especial “Los Pinos” de San Juan de Lurigancho, 2017 - Melendez Cruz, Erika Stefani (2018)
Objectives: Describe the strategies of adaptation of parents in the upbringing of children with Down syndrome that go to the Special Basic Education Center "Los Pinos" of San Juan de Lurigancho, 2017. Materials and Methods: The study was observational, descriptive level, non-experimental design. The sample consisted of 38 parents. Results: In relation to the strategy of the affective area, 55.3% stated that they were linked with other parents who have children with Down syndrome, while 18.4% reported that they sought spiritual support, 13.2% parents were informed about Down syndrome and with the same percentage of 13.2% corresponds to parents who sought emotional support. In health area strategies, 81.6% of parents affirm that their children currently receive therapies, and 18.4% do not receive therapies. Regarding children with SD who receive therapies 71% choose language therapy, 29% for language therapy along with the psychomotor. Regarding the strategy of the social area, 76.3% of parents stated that they did have the support of their family, and 23.7% report that they did not have family support. Within the group of parents who had family support, 44.8% mentioned that they had accepted their person and their child, and 13.8% said that family members helped take care of the child. And in the strategy of the educational area, in the beginning of the school life of the child with SD it is evident that 73.7% of the parents opted for their children to start their school life in a special education school, and in a lower percentage 26.3 % corresponds to parents who opted for the regular education college. Conclusion: Children are integrated into ordinary activities within the social and family environment. We must highlight the favorable behavior against the surrounding activities. Initially the parents show some degree of concern due to the difficulty to assimilate the situation regarding the status of their children.